Two-dimensional NaxSiS as a promising anode material for rechargeable sodium-based batteries: Ab initio material design : Luận văn ThS. Công nghệ nano (Chuyên ngành đào tạo thí điểm) - Pham, Thi Dung (2019)
Nowadays, energy security is the goal of many countries, including Vietnam. The shortage of energy, the effective use of recycling energy, and environmental pollution are emergency problems that demand strong efforts of scientists and governments. In general, energy comes from two sources: nonrenewable source (fossil carbon such as oil, coal, and gas) and renewable source (wind, water, sun). The excessive exploitation of fossil energy leads to serious environmental problems such as pollution, global warming, and ozone depletion. Therefore, the use of renewable energy is promoted to study and apply in the world, this essential solution is likely to deal with the lack of energy issue. However, the efficient storage of renewable energy is the big challenge because almost renewable resources are intermittent sources. Therefore, the study of efficient energy storage devices is extremely necessary. The various electricity storage devices were designed such as batteries, capacitors, and the other devices. Unlike primary batteries, secondary batteries are more popular for their charge and discharge abilities in use. The performance of rechargeable batteries is determined by theoretical capacity, voltage, electric conductivity, and life cycle parameters, strongly depends on electrodes and electrolyte materials. Therefore, the investigations to find out suitable materials for batteries have attracted much attention by both experiment and computational science. Today, thanks to the improvement in computational technology, researchers are making vigorous progress in the understanding of materials at atomic and molecular levels. With this understanding, we can select suitable materials for specific purposes and also improve advanced materials for applications. Aiming at enhancing the collaboration between experimental research and simulation work in studying on existing, and new materials as well as their application, computational material science with its techniques is applied to solve material relating problems. Moreover, computational experiments have an advantage over real experiments because most of the variables can be controlled in experiment processes. Nanotechnology may gradually take the forefront of scientists in the computational material science due to their nanoscale for several decades. At electronic level, density functional theory (DFT) is a popular method to investigate material characteristics in quantum physics. Regarding the requirement of stable storage electric devices and the demand of understanding material properties, we have investigated the performance of two-dimensional (2D) material as a promising anode for rechargeable batteries by simulation methods. In this research, electronic properties and stable structures of new materials Na-silicene sulfide were systematically investigated as a promising anode for rechargeable sodium-ion batteries.